Heinrich von Kleist : literary and philosophical paradigms - High, Jeffrey L.; Stewart, Rebecca, 1991-; Chen, Elaine (Studies in German literature, linguistics, and culture., 2022)
"Heinrich von Kleist (1777-1811) was a rebel who upset canonization by employing his predecessors and contemporaries as what Steven Howe calls "inspirational foils." It was precisely a keen awareness of literary and philosophical traditions that allowed Kleist to shatter prevailing paradigms. Though little is known about what specifically Kleist read, the frequent allusions in his enduringly modern oeuvre indicate fruitful dialogues with both canonical and marginal works of European literature, spanning antiquity (The Old Testament, Sophocles), the Early Modern Period (Shakespeare, De Zayas), the late Enlightenment (Wieland, Goethe, Schiller), and the first eleven years of the nineteenth century (Mereau, Brentano, Collin). Kleist's works also evidence encounters with his philosophical precursors and contemporaries, including the ancient Greeks (Aristotle) and representatives of all phases of Enlightenment thought (Montesquieu, Rousseau, Ferguson, Spalding, Fichte, Kant, Hegel), economic theories (Smith, Kraus), and developments in anthropology, sociology, and law. This volume of new essays sheds light on Kleist's relationship to his literary and philosophical influences and on their function as paradigms to which his writings respond"--